Hybrid procedure as a palliation approach in truncus arteriosus with interrupted aortic arch. (March 2020) - Mohsin, Muhammad; Ahmed, Waris; Karim, Farida; Sadqani, Saleem Akhtar
Abstract: Truncus arteriosus with interrupted aortic arch (Van Pragh A4) is a rare cyanotic heart disease. The management of this clinical entity is challenging due to obstructed systemic circulation, which required early intervention, especially in clinical setting with limited resources. Complete repair in early neonatal period associated with high morbidity and mortality. We present two patients with truncus arteriosus (type A4) palliated with hybrid procedure previously reported for management of patients with hypoplastic left heart syndrome. Highlights: This case report gives insight into a treatment strategy for low income countries with limited resources for truncus arteriosus type A4 by adapting a palliation in neonatal period which was previously described for hypoplastic left heart syndrome.